The burden of COVID-19 based on disability-adjusted life years: a systematic review of available evidence - Barfar, Eshagh; Raei, Behzad; Daneshi, Salman; Bagher Barahouei, Fatemeh; Hushmandi, Kiavash (Frontiers in Public Health, 2025)
BackgroundThe present study tries to evaluate and summarize the available evidence to provide insights into the COVID-19 burden worldwide using disability-adjusted life years (DALYs) and compare the level of damage across countries during this pandemic.MethodWe conducted a systematic review following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines to investigate the global burden of COVID-19. Studies were identified through searches conducted on Ovid Medline, Cochrane, Science Direct, Scopus, and PubMed databases as well as, the Google Scholar search engine. All stages of the search, study selection, qualitative assessment, and data extraction were carried out by two authors separately. Any disagreement among reviewers was resolved by discussion.ResultsThe total DALYs incurred by COVID-19 varied widely among nations, with rates per 100,000 population ranging from approximately 5 in Korea to 5,363 in the US. Deaths due to COVID-19 could substantially impact years of life lost (YLLs), emerging as a major contributing factor to DALYs. Furthermore, unlike in high-income countries, a significant proportion of YLLs in low- and middle-income countries is associated with individuals dying at younger ages. Years lived with disability (YLDs) were also identified as a minor contributing factor to DALY estimates associated with COVID-19.ConclusionOur findings from this investigation provide valuable insights into the impacts of COVID-19 on global health that may be an important basis for assessing its global burden, facilitating international comparisons, and allocating efforts to manage the epidemic. However, challenges persist in identifying and quantifying the economic costs and non-health effects of the event on an international scale.